Prospection and molecular analysis of CpGV isolates infecting Cydia pomonella at different geographical locations in Argentina - Arneodo Larochette, Joel Demian (2015)
The occurrence and genetic diversity of Cydia pomonella granulovirus infecting C. pomonella across Argentina were investigated. Larvae were collected from fruit orchards in regions where CpGV‐based biopesticides have been extensively used and then discontinued (Catamarca) or are still being used (Alto Valle). The survey was also extended to regions where few occasional (i.e. Mendoza) or no virus treatments (various locations) have been made. PCR analysis showed an unexpectedly high proportion of infected larvae (31.3–50%) at most sampling sites in Catamarca. Phylogenetic analysis of these samples, based on gran and lef‐8 genes partial sequences, revealed a previously unreported CpGV variant which could not be assigned to any of the known CpGV genome types and formed a well‐defined new cluster. Instead, samples from Alto Valle were genetically similar to isolate CpGV‐M (the active ingredient in commercial formulations). There, the percentage of infected individuals was considerably lower (1.8–21.9%). The virus was not detected in Mendoza or the other sampling regions. Implications of these results on the epidemiology and current classification of CpGV isolates are discussed.